Mechanical Studies on Chitosan Functionalized Multiwalled Carbon Nanotube Reinforced Epoxy Bionanocomposites - Wu*, Yuhua; Wang, Ning; Bai, Hongcun (Asian Journal of Chemistry, 2014)
The chitosan functionalized multiwalled carbon nanotubes reinforced epoxy bionanocomposite (CS-g-MWCNTs/EP) was developed. Chitosan (CS) was grafted to multiwalled carbon nanotubes (MWCNTs), first by reacting the oxidized carbon nanotubes (MWCNT-COOH) with thionyl chloride to form acyl-chlorinated multiwalled carbon nanotubes (MWCNT-COCl) followed by subsequent dispersion in chitosan. The chitosan grafted multiwalled carbon nanotubes (CS-g-MWCNTs) were reinforced in the epoxy matrix using high speed stirrer and then cured. The TEM of CS-g-MWCNTs shows a visible coating of chitosan on the surface of MWCNTs. FT-IR spectra of CS-g-MWCNTs indicate an overlap of the amide band and the free amino groups of the chitosan. The mechanical properties such as tensile and impact strength of epoxy matrix increases to 16 and 52 %, respectively by the reinforcement of 1.5 wt. % CS-g-MWCNTs, which clearly reveals that the free amino groups of CS-g-MWCNTs acted as a curing agent and was covalently attached into epoxy matrix. Morphologies of pure chitosan, MWCNT, MWCNT-COOH and CS-g-MWCNTs/EP bionanocomposites were studied by scanning electron microscope.